Effectiveness of Interactive Instructional Media on Electrical Circuits - Puyada, Deno; Ganefri, G; Ambiyar, A; Ema Wulansari, Rizky; Herawan Hayadi, B (International Journal of Engineering and Technology, 2018)
Based on observation toward students of Electrification Engineering, the result explained limitation of interactive instructional media so that teacher had not found the good way to teach the lesson who could not teach with conventional method. These phenomena could bring negative effects for students, so that the students might reply the lesson, and could make time fly. This study aimed to know about effectiveness of interactive instructional media on Electrical Circuits. This research uses Research and Development (R&D) method and development model in this research was 4D (four-D), there were four steps in this model –define, design, develop, and disseminate–. The result that is obtained from this research was follow: The effectiveness of interactive instructional media was expressed effective for improving the students’ outcomes because with 90.6% of students had reached Minimum Mastery Criteria. Based on the results of this research could be conclude that interactive learning media for Electrical Circuits was effective to be used as a learning media.